The media image of women in Kurdish television is a field survey - Karadakhi, Assistant Professor Dr. Bahat Hasib (Sulaimani Journal for Humanities, 2026)
A segment of Kurdish visual media has been distorting facts for years, portraying a negative and unfair image of women. Women should be seen as human beings with duties and responsibilities, and with equal rights to employment and creative opportunities within society, not as subordinate to men, deprived of their talents and aspirations. This study focuses on the position of women and the media image shaped by Kurdish satellite and local television channels. As a result, we concluded that a number of Kurdish television stations promote a media image that oppresses women and contributes to reinforcing negative, traditional stereotypes in the minds, imaginations, and memories of individuals and the public.